Design, Fabrication, and Testing of a Raspador for Simultaneous Extraction and Brushing of Sisal Fibers by Small-scale Sisal Farmers - Barasa, N. W.; Njoroge, K. D.; Mbuya, T. O. (Taylor & Francis, 2021)
Demand for natural fibers is on the rise as awareness of environmental protection keeps abreast. Sisal fibers, for instance, are largely utilized not only in the manufacture of mats, ropes, carpets, and sacks but also in the reinforcement of polymer composites. With the increased demand for sisal fibers, there is a need to equally increase the exploitation of sisal by smallscale farmers. UNIDO, for instance, recommended that appropriate smallscale machines that are accessible to small-scale holders should be developed. This research examines the progress in the development of small-scale machines and designs a raspador for simultaneous extraction and brushing of sisal fibers. This is to ensure that there is value and income addition for the small-scale farmers in East Africa and perhaps the rest of the world.
Keywords: Raspador; design; fabrication; testing; sisal fibers; extraction; brushing